2022
DOI: 10.1002/edn3.334
|View full text |Cite
|
Sign up to set email alerts
|

Warm temperature and alkaline conditions accelerate environmental RNA degradation

Abstract: Recent developments in environmental DNA (eDNA) analysis allow more rapid and extensive biomonitoring than traditional capture‐based surveys do. However, detection of eDNA not derived from living organisms may lead to false‐positive inferences of species presence. Such limitations may be overcome by utilizing RNA molecules present in the environment (environmental RNA [eRNA]) because of their physiochemical instability. Nevertheless, the biomonitoring performance of eRNA analysis remains unclarified because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 60 publications
(100 reference statements)
0
58
3
Order By: Relevance
“…Throughout water sampling and ltration, disposable gloves and masks were worn to prevent RNase contamination in the water samples. All equipment for water ltration ( lter funnels and tweezers) was bleached before use in 0.1% sodium hypochlorite solution for at least 5 min (Yamanaka et al, 2017;Jo et al, 2022).…”
Section: Water Samplingmentioning
confidence: 99%
See 3 more Smart Citations
“…Throughout water sampling and ltration, disposable gloves and masks were worn to prevent RNase contamination in the water samples. All equipment for water ltration ( lter funnels and tweezers) was bleached before use in 0.1% sodium hypochlorite solution for at least 5 min (Yamanaka et al, 2017;Jo et al, 2022).…”
Section: Water Samplingmentioning
confidence: 99%
“…Then, using a PrimeScript RT reagent kit with gDNA Eraser (Perfect Real-Time; Takara Bio Inc., Japan), gDNA was enzymatically removed from the eRNA extracts (in total, two rounds of gDNA removal) and complementary DNA (cDNA) was immediately synthesized (Jo et al, 2022). Following the manufacturer's instructions, 20 µL of cDNA sample was prepared from 7 µL of each eRNA extract, for which random and oligo dT primers were used for reverse transcription.…”
Section: Rna Extraction and Complementary Dna (Cdna) Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Qian et al 21 investigated the temperature effects on the stability of F. chinensis eDNA/eRNA and found that eRNA showed a faster degradation if temperature was increased, and the stability was maintained across the range of temperature. Furthermore, Kagzi et al 21 reported eRNA of Daphnia pulex degrades more rapidly than eDNA across a broad range of pH condition and Jo et al 22 reported that warm temperature and alkaline conditions accelerate the degradation rate of Danio rario eRNA. The degradation rate of eRNA would vary according to species, genes, environmental conditions, and analytical method.…”
Section: Introductionmentioning
confidence: 99%